2013
DOI: 10.1103/physrevb.87.174109
|View full text |Cite
|
Sign up to set email alerts
|

XANES and EXAFS study of the local order in nanocrystalline yttria-stabilized zirconia

Abstract: The local order around Zr and Y atoms of nanocrystalline yttria-stabilized zirconia (YSZ) powders with different grain sizes has been investigated by x-ray absorption spectroscopies. The samples were prepared by means of mechanical alloying with or without subsequent sintering treatment and also by milling commercial YSZ. Our study is motivated by the interest in the electrical properties of grain boundaries and the controversy about the level of disorder in the intergrain regions in nanocrystalline YSZ. The x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
7
25
0
Order By: Relevance
“…Similarly, the energy position of the D and E structures shifts towards higher energies for the cubic phase. The latter results indicate the decrease of the first neighbors Zr-O interatomic distance upon a tetragonalto-cubic transformation, in agreement with previous results found for YSZ compounds [33][34][35][36][37][38]. The variation of the B/C intensity ratio is also related to the different crystal structure.…”
Section: Zr and Y K-edge Xanes And Exafs Characterizationsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, the energy position of the D and E structures shifts towards higher energies for the cubic phase. The latter results indicate the decrease of the first neighbors Zr-O interatomic distance upon a tetragonalto-cubic transformation, in agreement with previous results found for YSZ compounds [33][34][35][36][37][38]. The variation of the B/C intensity ratio is also related to the different crystal structure.…”
Section: Zr and Y K-edge Xanes And Exafs Characterizationsupporting
confidence: 92%
“…4(b), the Zr K-edge k 3 -weighted EXAFS signals of both tetragonal 2Y12T2h and cubic YZS c-10 samples show differences in the relative intensity of several spectral features, marked with arrows in Fig. 4(b) [33][34][35][36][37]. This comparison clearly shows the coincidence of the EXAFS spectra of both the cubic phase in the 10Ti8h and 15Ti2h duplex samples and of the cubic c-10 sample, which increases the level of confidence in the procedure we have followed.…”
Section: Fig 4 (Color Online) (A)mentioning
confidence: 97%
See 1 more Smart Citation
“…As the concentration of yttria in the films increases, the absorption edge becomes broader and then splits into two. When compared with theoretical spectra of different phases of zirconia, it is inferred that XANES spectra for films A, B and C agree with presence of predominant monoclinic, tetragonal and cubic phases respectively as reported by Dura et al [31]. Fig.…”
Section: Resultssupporting
confidence: 74%
“…It can also be observed that no Zr Zr correlation is found in these samples except a small peak between 3 and 4Å for film B indicating that the cation-cation network is more ordered in this tetragonal dominated film as compared to the other two films which corroborates the XRD results also as described above. As reported by Dura et al there is amplitude reduction of peak corresponding to Zr Zr correlation in Fourier transform of nanocrystalline materials and hence no Zr Zr correlation is found for films A and C [31].…”
Section: Resultsmentioning
confidence: 48%